The integration of surgical and dermatological techniques in the treatment of cutaneous aging: multidisciplinary approaches and clinical outcomes - a comprehensive systematic review of current literature - Portilla, Andrés S. P.; Portilla, Camila S. P.; Palacios, Gabriela S. G.; Rodríguez, Bryan S. P.; Castillo, Sandra G. A.; Espin, Nathalie E. P.; Pita, Gina P. M. (International Journal of Research in Medical Sciences, 2024)
This comprehensive review explores the integration of surgical and dermatological techniques in treating cutaneous aging, highlighting the evolution of anti-aging strategies towards more refined and less invasive methods. As aging skin results from a combination of intrinsic and extrinsic factors, leading to structural and physiological changes, dermatology has advanced to offer multifaceted treatment approaches. We aimed to review advances and evolution in surgical interventions such as facelifts and blepharoplasty. We will discuss noninvasive and minimally invasive techniques, such as Ultherapy and fat grafting, which are widely used and are the best alternatives to traditional surgery. Other techniques, such as thread lifts and novel materials like polydioxanone (PDO) and polylactic acid (PLA) threads, are also reliable techniques for minimally invasive facial rejuvenation.